THE FAMILY, CULTURE AND SUSTAINABLE DEVELOPMENT - Mildred, Ekot O. (Acta Scientiae et Intellectus, 2024)
Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. The family has been the basic unit of change in every culture. Unfortunately, the concept of sustainable development has failed to focus the family. It is within families that sustainable lifestyles, decisions and change that can positively impact future generations are encouraged or undermined. In addition, global sustainable development can only be achieved if families as basic unit of human societies achieve sustainability in all areas. It is from the base of a sustainable family that individuals are best able to contribute positively to society as a whole. Families operate within the dictates of culture; as such culture has an important role in families’ decision making, consumption, relationship patterns, and conflict resolution; and in creating sustainable families. The family is also identified in a cultural context; culture defines roles and rules of conduct of family members; while families are also assessed by standards inherent in the culture. This paper therefore argues that making our homes and families more sustainable within the dictates of our culture is the panacea for global sustainable development.